REVITALISASI PROGRAM NUSA TENGGARA ASSOCIATION (NTA) DALAM PENANGGULANGAN KEMISKINAN DI KABUPATEN SIKKA, NUSA TENGGARA TIMUR TAHUN 2020-2024 - Diani, Fitri; Renolafitri, Hendrini; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Sikka Regency, East Nusa Tenggara (NTT), is a region facing complex poverty challenges, exacerbated by its dry agro-ecological conditions and the limitations of government development programs. In this context, non-governmental organizations (NGOs) such as the Nusa Tenggara Association (NTA) play a crucial role. This research aims to analyze the revitalization of NTA's efforts in alleviating poverty in Sikka during the 2020–2024 period. Using a qualitative research method with a case study approach, data were collected through a literature review of NTA reports and in-depth interviews with NTA staff at both central and field levels. The analysis was conducted using David Lewis's theory of NGO roles (implementer, catalyst, partner) and a constructivist perspective. The findings reveal a strategic shift in NTA's approach, moving from a predominantly distributive model (aid provision) to the transfer of adaptive, sustainable agricultural technology. This revitalization included introducing grafting techniques for rejuvenating cocoa and cashew trees, developing horticulture based on rainwater harvesting tanks and bokashi compost, and modernizing pig farming through hygienic stalls and an artificial insemination (AI) program. NTA's role evolved from merely an implementer to a catalyst for change and a strategic partner for the government. The formal collaboration with the Agricultural Technology Assessment Institute (BPTP)/BRIN proved effective, with innovations initiated by NTA later being adopted by local government programs. This demonstrates NTA's success in influencing local development practices, contributing to an increase in the income of assisted households and a reduction in Sikka's overall poverty rate. Keywords: NTA, Poverty, Sikka, NGO, Agricultural Development, Revitalization, Technology Transfer